Kuasa Wacana Keagamaan : dari Kekerasan Simbolik menuju Kekerasan Fisik - Ulya Ulya (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
This article aims to show the rise of violence in society. One of its causes is the power of religious discourse. The issue departs from the moslems who do their religious teaching always refer to the texts of religious discourse. While the texts that they refer, from one to others, are different.It is no problem if the texts that they refer are used as a basis to improve the quality of their religiousity in the private life. On the other hand, if it is also to judge or classify others who disagree in the public, it is very dangerous. Because it is aware or not, it will discriminate and dominate others by using the basis of religious discourse. Discrimination and domination by using religious discourse are called symbolic violence. And actually, this symbolic violence bocomes the root of emergence of physical violence